Diagnostic value of a urine test in pregnancy of unknown locationAJOG Global Reports at a Glance - Andy Schmitt, MD; Claire Tourette, MD; Audrey Pivano, MD; Caroline Rambeaud, MD; Anderson Loundou, MD; Aubert Agostini, MD, PhD (AJOG Global Reports, 2023)
BACKGRO: Pregnancy of unknown location (PUL) is a term used when there is a positive pregnancy test but no sonographic evidence for an intrauterine pregnancy (IUP) or ectopic pregnancy (EP). This term is a classification and not a final diagnosis. OBJECTIVE: This study aimed to evaluate the diagnostic value of the Inexscreen test on the outcome of patients with pregnancies of unknown location. STUDY DESIGN: In this prospective study, a total of 251 patients with a diagnosis of pregnancy of unknown location at the gynecologic emergency department of the La Conception Hospital, Marseille, France, between June 2015 and February 2019 were included. The Inexscreen (semiquantitative determination of intact human urinary chorionic gonadotropin) test was performed on patients with a diagnosis of pregnancy of unknown location. They participated in the study after information and consent collection. The main outcome measures (sensitivity, specificity, predictive values, and the Youden index) of Inexscreen were calculated for the diagnosis of abnormal pregnancy (nonprogressive pregnancy) and ectopic pregnancy. RESULTS: The sensitivity and specificity of Inexscreen for the diagnosis of abnormal pregnancy in patients with pregnancy of unknown location were 56.3% (95% confidence interval, 47.0%–65.1%) and 62.8% (95% confidence interval, 53.1%–71.5%), respectively. The sensitivity and specificity of Inexscreen for the diagnosis of ectopic pregnancy in patients with pregnancy of unknown location were 81.3% (95% confidence interval, 57.0%–93.4%) and 55.6% (95% confidence interval, 48.6%–62.3%), respectively. The positive predictive value and negative predictive value of Inexscreen for ectopic pregnancy were 12.9% (95% confidence interval, 7.7%–20.8%) and 97.4% (95% confidence interval, 92.5%–99.1%), respectively. CONCLUSION: Inexscreen is a rapid, non–operator-dependent, noninvasive, and inexpensive test that allows the selection of patients at high risk of ectopic pregnancy in case of pregnancy of unknown location. This test allows an adapted follow-up according to the technical platform available in a gynecologic emergency service.